اشتراط الولاية في عقد النكاح: دراسة تحليلية مقارنة بين ابن حزم في المحلى بالآثار وابن رشد في بداية المجتهد - Bbaale, Hussein (Journal of Islamic Studies and Arabic Language, 2023)
This research aims to highlight the relationship between the text contained in the book “Al-Muhalla bil-Athar” by Ibn Hazm Al-Zahiri Al-Andalusi(d. 595/1198) and the one contained in the book Bidayat al-Mujtahid wa Nihayat al-Muqtasid by Ibn Rushd al-Hafid (d. 595/1198) on the issue of the requirement of guardianship in marriage. It also shows the contexts that could have a role in guiding the way the two imams dealt with the issue under study. To achieve the objectives of the research, the researcher used inductive, analytical, and comparative approaches in understanding and analyzing the way they dealt with the issue and the impact of different contexts in guiding their approach. The research concluded that there are common denominators between Ibn Hazm and Ibn Rushd in their courses, but the method of each of them in dealing with the issue differs from the other.